Pengembangan Buku Petunjuk Praktikum Ekologi pada Materi Keanekaragaman Hayati - Baihoki, Muhammad Hamzan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
This research aims to develop an ecology practical manual on biodiversity material. The type of research used in this research is development research. Research into the development of ecological practicum instructions uses the 4D model (Define, Design, Develop, and Disseminate), but in Indonesian terms it has been adapted to become the 4P model (Define, Design, Develop, and Disseminate). In this development research, the researcher only reached the development stage (3P model) which was validated by three expert validators (suitability of content, language and graphic design) as well as a readability test by students. The instrument used in this research is in the form of a validation sheet which was given to three expert validators to be corrected so that the teaching materials created were suitable for use or not. Meanwhile, the readability test was tested on 15 students, the results of which were used to assess whether the practical instructions were suitable for use or not. Based on the research results, it was found that the validation value from content suitability experts was 88%, the validation value from language experts was 83%, and the validation value from graphic design experts was 82%. So the average value of the three expert teams is 84% ​​with the conclusion that it does not need to be revised. Meanwhile, the readability test by 15 students with an average score of 3.92 is suitable for use without revision. Therefore, the teaching materials in the form of practical manuals that have been developed are suitable for use as a guide without revision.